Biharmonic constant Π₁-slope curves according to type-2 bishop frame in Heisenberg group Heis³ - Talat Körpinar; Essin Turhan (Boletim da Sociedade Paranaense de Matemática, 2014)
In this paper, we introduce constant Π₁- slope curves according to type-2 Bishop frame in the Heisenberg group Heis³. We characterize the biharmonic constant Π₁- slope curves in terms of their Bishop curvatures. Finally, we find out their explicit parametric equations in the Heisenberg group Heis³. Additionally, we illustrate our main theorem.